The impact of the Russia-Ukraine conflict on market volatility: stability of Islamic cryptocurrency - Hasyim, Fuad; Rusgianto, Sulistya; Setianingsih, Hesti Eka; Fauziah, Nurul; Ramly, Arroyan (Universitas Islam Negeri Walisongo Semarang, 2024)
Purpose - This research investigates how the Russia-Ukraine conflict affects the volatility of cryptocurrencies, with a specific focus on the comparative stability of Islamic gold-backed cryptocurrencies versus conventional cryptocurrencies, such as Bitcoin.Method - Utilizing the GARCH model, this study examines the risk factors and volatility transmission among cryptocurrencies (Bitcoin and Tether-gold), traditional financial markets (gold and stock markets), and their interrelationships during the conflict period. The study employs the daily closing prices of Bitcoin, Tether-gold, gold, the S&P 500, and the Dow Jones Islamic Market Index from February 7, 2020, to November 30, 2023.Result - Bitcoin experienced significant volatility during the conflict, while the Tether-gold remained more stable. Islamic gold-backed cryptocurrencies have proven to be more stable than conventional ones during geopolitical crises.Implication - The findings offer valuable insights for investors seeking safe-haven assets during periods of economic uncertainty. Gold-backed cryptocurrencies present a more stable investment option compared to conventional cryptocurrencies, especially for investors adhering to Shariah principles.Originality - This research highlights the stability of Islamic gold-backed cryptocurrencies during geopolitical events, contributing to the understanding of safe-haven assets and offering practical implications for portfolio diversification and risk management.